Of potential new treatment targets and polythetic approach in meningoencephalitis of unknown origin: a review - Nessler, Jasmin N.; Tipold, Andrea (Frontiers in Veterinary Science, 2024)
Meningoencephalitis of unknown origin (MUO) represents an umbrella term for inflammatory, non-infectious central nervous system (CNS) diseases in dogs. Current therapeutic approaches, involving long-term glucocorticosteroid use, often fail to provide adequate relief or cure, and the effectiveness of additional immunosuppressive medications remains uncertain. Future advancements in MUO treatment may benefit from patient-specific therapies, potentially enhancing treatment precision, efficacy, and minimizing side effects. However, significant challenges impede this progress, including ambiguity in MUO subtype classification, uncertainties regarding the autoimmune nature vs. infectious triggers, and the lack of reliable diagnostic biomarkers. Clinical heterogeneity and overlapping signs with other encephalopathies further complicate diagnosis and treatment. This review gives an overview about diagnostic findings and immunological features of MUO. It advocates for a more overall characterization of MUO by using a polythetic system to better characterize MUO subtypes, identify immunological treatment targets, and establish a conceptual foundation for future therapeutic trials. Addressing these themes may lead to more effective and less burdensome treatments, improving the quality of life for dogs afflicted with MUO and their owners.